Association between cord blood IgE levels in newborns and family history of atopic diseases - Andhika T. Hutapea; Budi Setiabudiawan; Myrna Soepriadi; Diet Sadiah Rustama (Indonesian Pediatric Society, 2006)
Background Cord blood-IgE (CB-IgE) levels have been usedwidely as a specific marker of atopic diseases. In some previousstudies, CB-IgE levels in subjects with and without a family historyof atopic diseases have been controversial.Objective To determine the CB-IgE level in newborns and to iden-tify the association between CB-IgE and family history of atopicdiseases.Methods A cross-sectional study was done to compare the CB-IgElevels in neonates with or without a family history of atopic diseasesin mother, father, or siblings. Subjects of this study were 124 new-borns who consecutively born in Puskesmas Kiaracondong,Bandung, during the period of March 2001 to July 2002. Subjectswere divided into 2 groups based on history of atopic diseases.Measurements of CB-IgE levels were done by sandwich ELISAmethods. Data were analyzed by c 2 statistics, t test, ANOVA, andDunkan’s test.Results The mean CB-IgE levels in the group with and without afamily history of atopic diseases were 3.2±2.5 IU/ml and 0.5±0.5IU/ml (P<0.001), respectively. The mean CB-IgE levels in maleand female infants with a family history of atopic diseases were3.3±2.7 IU/ml and 3.03±2.2 IU/ml (P>0.05), respectively. Basedon the cut-off point (1.3 IU/ml), CB-IgE levels had significant posi-tive association with a family history of atopic diseases (OR 156,95%CI 29.61;1104.24). CB-IgE levels in neonates with 1, 2, and 3atopic family members were 1.67±0.78 IU/ml, 3.76±2.11 IU/ml, and6.6±2.7 IU/ml, respectively (F=32.603; P<0.001).Conclusion Most newborns with a family history of atopic dis-eases showed high levels of CB-IgE, but there were no correlationwith gender. The probability of having atopic diseases increase inconcord with the number of family with atopic diseases